Occurrence of traffic violence according to psychological factors and mental disorders: a narrative review (Brazilian Journal of Health Research, 2025)
Introduction: Traffic violence is analyzed as a complex phenomenon, involving risky behaviors and the violation of traffic rules. Objective: To survey the main findings regarding the relationship between traffic violence and psychological factors and mental disorders. Methods: This is a narrative literature review, with an electronic search conducted by the researcher between 2019 and 2023 in the Virtual Health Library (BVS). The guiding question of the study was: “Which psychosocial factors are involved in traffic violence?”. The search expression used was: (violence) AND ((drivers) OR (traffic)). A semantic analysis of the data was performed. Results: The results indicate the influence of conditions such as anxiety, depression, irritability, and emotional dysregulation on impulsive and aggressive driver behavior, as well as the importance of emotional self-regulation and the impact of sleep deprivation on decision-making and traffic violations. Conclusion: The reviewed studies reveal the complexity of psychological factors influencing behavior in traffic, with emphasis on anxiety and depression among drivers.
Keywords: Road rage; Violence; Mental disorders; Emotional regulation